Evaluation of Performance Allowance Policy in the Bandung City Office Education - Wibowo, Muhamad Dwicahya Gentur Wibowo; Budiman Rusli; Elisa Susanti (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2024)
Evaluations serve as a valuable instrument for democratic governments, offering a foundation for accountability and facilitating policy learning. Bandung Mayor Regulation Number 58 of 2020 concerning Employee Performance Appraisal, a regional policy applicable in Bandung City, is to calculate and receive fair and measurable performance allowances in line with the achievement of individual and organizational performance goals. This article aims to evaluate the implementation of the performance allowance policy in the last three years at the Bandung City Education Office. This study uses qualitative methods, collecting subjective data from informants' perspectives. The results of the evaluation found that the Evaluation of the Performance Allowance Policy at the Bandung City Education Office has been practical, efficient, good enough in terms of the nominal allowances given, equality in policy implementation, responsive to developments, appropriate in overcoming performance problems and employee welfare at the Bandung City Education Office. The evaluation found that the policy improved employee welfare, addressed performance issues effectively, and was responsive to organizational changes